Preparation and Evaluation of Sesame oil loaded β-Cyclodextrin sponges for topical delivery - Vekariya Hitesh; Patil Priti; Krishna Chaitanya J. (E3S Web of Conferences)
The activity of above drug can be improved and its toxicity can be diminished by enhancing the release pattern of active constituents. The creation of polymer-based sponges for the treatment of topical disease was the goal of this project. The rationale of the current study was to study the sponge drug delivery system for improving solubility, better encapsulation and therapeutic effectiveness of sesame oil by the development of sponges. A preliminary protocol was set up for screening of formulation components. β-cyclodextrin with DPC were used as polymers, cross-linkers. sesame oil sponges were fabricated by Polymerisation methods. Formulation of drug in liposome also create a problem that, after rupturing a liposome drug get suddenly release and causes accumulation at site. To avoid accumulation, irritation and for moderate release pattern sesame oil can be incorporate into the sponge having less pore size. The aim of this work was to create β- cyclodextrin containing Sesame oil sponges. Sesame oil first identified by using Gas chromatography and other monographic evaluation also done. Polymerisation method was used for the preparation of Sesame oil sponges. The production yield, PXRD, particle size, and encapsulation efficiency of the sustained release formulation were evaluated and visualized by scanning electron microscope (SEM). The results showed that all prepared sponges were spherical in form and covered many pores. The production yield was in 98±0.20 Entrapment efficiency was in 86.64% and particle size was 20-50nm. The results demonstrated that β- cyclodextrin based Sesame oil sponges was successfully formulated.